Feasibility of HIV-1 RNA Extraction and Viral Load Testing of Bone Marrow Plasma Using the Abbott m2000 Platform and RealTime Quantitative HIV-1 Assay - Jason Rippe; William Kabat; Kristian Schafernak; Ram Yogev (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2017)
Current efforts to fi nd a cure for HIV disease require that viral load assays be available to accurately detect and measure viral load in compartments other than peripheral blood. Over the years, HIV viral load assays have been adapted to measure viral presence in cerebral spinal fl uid (CSF), genital secretions and various other compartments. In this study we describe our efforts to quantitatively recover HIV-1 from pooled pediatric bone marrow plasma spiked with known concentrations of HIV-1 virus using the Abbott RealTime HIV-1 assay and the m2000 platform. We focused on nucleic acid extraction, sample dilution, viral copy recovery, linearity and limit of detection. We found that HIV-1 viral load can be reliably detected down to 250 copies/mL in bone marrow plasma diluted with BM53-processed EDTA plasma and extracted with the Abbott mSystem. The assay was linear from 250 to 100,000 copies/mL. Bone marrow composition may contribute to some loss of HIV-1 recovery,and a high quality serum diluent is essential for optimal viral recovery and detection. Our results suggest that the Abbott RealTime HIV assay with the m2000 platform is a useful method to quantify HIV-1 viral load in human bone marrow.